TANGGAPAN PRESIDEN JOKOWI TERHADAP WACANA PENUNDAAN PEMILU (Analisis Framing Kompas.com, Mediaindonesia.com dan Sindonews.com) - Fadlan, Muchammad (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2022)
The discourse of postponing the 2024 election or extending the term of office of the President has become a conversation in the public sphere and has been reported in various media. The President as the official being discussed has given his response to the discourse. This study aims to analyze the news framing of the President's response to the discourse on election postponement and term extension by various media such as Kompas.com, Mediaindonesia.com and Sindonews.com in the period 5 March – 15 March 2022. Robert N. Entman framing analysis and descriptive method Qualitative research is used to determine the framing of news by these media. The results of the study found that reports from Sindonews.com and MediaIndonesia.com tended to frame that the President had adhered to the constitution regarding his term of office and had no intention of delaying the election or increasing his term of office. Only the people around him tried to work on the discourse. The media, Kompas.com, has a tendency to have doubts about the President's statement, by displaying news of the President's statements in the past. All the media can be concluded to have paid more attention to the discourse of postponing the election in their headlines.